2018
DOI: 10.1155/2018/2694679
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Imaging and Biological Evaluation of the Radiosensitizing Effect of Oleanolic Acid

Abstract: Background and Purpose The aim of this study was to evaluate the radiosensitizing effect of oleanolic acid (OA) on C6 rat glioma and the changes in tumor biology during radiosensitization therapy on 18F-fluoromisonidazole (18F-FMISO) positron emission tomography/computed tomography (PET/CT). Methods The radiosensitizing effect of OA on C6 tumors was assessed in vivo by measuring the tumor inhibitory rate and rat survival time. Meanwhile, rats with C6 tumors were imaged with 18F-FMISO PET/CT during radiosensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Interestingly, FMISO uptake correlates with the “gold standard” of tissue measurement using invasive polarographic oxygen electrodes ( 8 , 9 ), as well as pimonidazole uptake in animals with glioma ( 10 ). Our previous and several other studies have reported decreased FMISO uptake in hypoxic tumors during radiotherapy and post-treatment, indicating that reoxygenation occurs ( 11 16 ). However, cancer cells killed by irradiation no longer show FMISO uptake; thus, it is hard to correctly determine whether reduced FMISO uptake in radiotherapy results from tumor reoxygenation or reflects tumoricidal effects.…”
Section: Introductionmentioning
confidence: 60%
“…Interestingly, FMISO uptake correlates with the “gold standard” of tissue measurement using invasive polarographic oxygen electrodes ( 8 , 9 ), as well as pimonidazole uptake in animals with glioma ( 10 ). Our previous and several other studies have reported decreased FMISO uptake in hypoxic tumors during radiotherapy and post-treatment, indicating that reoxygenation occurs ( 11 16 ). However, cancer cells killed by irradiation no longer show FMISO uptake; thus, it is hard to correctly determine whether reduced FMISO uptake in radiotherapy results from tumor reoxygenation or reflects tumoricidal effects.…”
Section: Introductionmentioning
confidence: 60%
“…However, 15 mg/kg/d (for 10 d) of UA did not affect the tumour size in an orthotopic glioma model in vivo [ 126 ]. In another study utilizing an in vivo model of glioblastoma, the anti-tumour effects of triterpenoids have been established [ 127 ]. When C6 tumour-bearing rats were given OA solution by gavage (40 mg daily for 7 d) and underwent irradiation therapy, the combined effect of OA and radiation was demonstrated, which resulted in the decreased growth rates of tumours and the prolonged survival period of tumour-bearing rats.…”
Section: Neuroprotective Effects Of Ursolic and Oleanolic Acidsmentioning
confidence: 99%
“…Wang et al used C6 glioma model rats to evaluate the radiosensitization effects of oleanolic acid with FMISO [62]. They observed slowed tumor growth by the OA treatment combined with radiotherapy, as well as a decrease in FMISO uptake, and they suggested that FMISO PET can be of value for radiosensitization response evaluations.…”
Section: The Clinical Usefulness Of Fmisomentioning
confidence: 99%